Towards improvement of the operation and safety of European nuclear power plants through enhanced thermal-hydraulics experiments and analysis - Zwijsen Kevin; Papukchiev Angel; Montout Michaël (EPJ Nuclear Sciences & Technologies)
Due to the negligible levels of CO2 it produces, nuclear energy is gaining a more prominent role in the current transition to clean energy. An important aspect to nuclear energy generation is the safety of nuclear installations. To ensure safe operation of nuclear reactors, all facets must be carefully monitored and controlled, and the behavior of the operational and safety systems must be assessed in detail under normal and off-normal conditions. A key aspect herein is the reactor thermal-hydraulics, crucial to ensure heat generated in the core gets transferred to the secondary system, during electricity generation, or designated heat sinks, for emergency scenarios. Two European projects focusing on reactor thermal-hydraulics recently received grants within the Euratom to perform four year research that will enhance the operation and safety of the European nuclear power reactors. PASTELS (PAssive Systems: Simulating the Thermal-hydraulics with ExperimentaL Studies) deals with innovative passive safety systems and investigates the possibility of using reliable experimental data to assess the ability of various European thermal-hydraulic tools to simulate the behavior of these systems. GO-VIKING (Gathering expertise On Vibration ImpaKt In Nuclear power Generation), on the other hand, focuses on the hydraulic interaction between the coolant and crucial nuclear power plant components that are susceptible to flow-induced vibrations. Through experimental and numerical investigations, these interactions are further studied and improved modeling methodologies are developed. In the current paper, the global objectives of both projects, as well as the methodologies and the expected impacts are presented. Moreover, selected results are briefly discussed and conclusions are drawn.